Fusobacterium nucleatum tumor DNA levels are associated with survival in colorectal cancer patients - Kunzmann, Andrew T; Proença, Marcela Alcântara; Jordao, Haydee Wt; Jiraskova, Katerina; Schneiderova, Michaela; Levy, Miroslav; Liska, Václav; Buchler, Tomas; Vodickova, Ludmila; Vymetalkova, Veronika; Silva, Ana Elizabete; Vodicka, Pavel; et al. (European journal of clinical microbiology & infectious diseases, 2019)
There is increasing evidence indicating a role for Fusobacterium nucleatum (F. nucleatum) in colorectal cancer (CRC) development and prognosis. This study evaluated F. nucleatum as a prognostic biomarker, by assessing its association with post-diagnosis survival from CRC. From September 2008 to April 2012 CRC patients (n = 190) were recruited from three hospitals within the Czech Republic. F. nucleatum DNA copies were measured in adjacent non-malignant and colorectal tumor tissues using quantitative real-time PCR. Cox Proportional Hazards (HR) models were applied to evaluate the association between F. nucleatum DNA and overall survival, adjusting for key confounders. Risk prediction modeling was conducted to evaluate the ability to predict survival based on F. nucleatum status. High, compared with low, levels of F. nucleatum in colorectal tumor tissues were associated with poorer overall survival (adjusted HR 1.68, 95% CI 1.02-2.77), which was slightly attenuated after additional adjustment for microsatellite instability status. However, inclusion of F. nucleatum in risk prediction models did not improve the ability to identify patients who died beyond known prognostic factors such as disease pathology staging. Although the increased presence of F. nucleatum was associated with poorer prognosis in CRC patients, this may have limited clinical relevance as a prognostic biomarker.
Keywords: Colorectal Neoplasms; Cohort Studies; mužské pohlaví; Colorectal neoplasm; Male; infekce bakteriemi rodu Fusobacterium; senioři; senioři nad 80 let; analýza přežití; Czech Republic; Fusobacterium Infections; Female; Humans; Prognosis; kohortové studie; lidé; Risk Assessment; DNA bakterií; Fusobacterium nucleatum; kvantitativní polymerázová řetězová reakce; ženské pohlaví; lidé středního věku; Middle Aged; Real-Time Polymerase Chain Reaction; Česká republika; Disease survival; DNA, Bacterial; prognóza; Aged, 80 and over; Biomarkers; biologické markery; kolorektální nádory; Survival Analysis; Colorectal cancer; Bacterial infection; Aged; hodnocení rizik